On‐Demand Dissolution of a Dendritic Hydrogel‐based Dressing for Second‐Degree Burn Wounds through Thiol–Thioester Exchange Reaction. Issue 34 (13th July 2016) - Konieczynska, Marlena D.; Villa‐Camacho, Juan C.; Ghobril, Cynthia; Perez‐Viloria, Miguel; Tevis, Kristie M.; Blessing, William A.; Nazarian, Ara; Rodriguez, Edward K.; Grinstaff, Mark W.
Abstract: An adhesive yet easily removable burn wound dressing represents a breakthrough in second‐degree burn wound care. Current second‐degree burn wound dressings absorb wound exudate, reduce bacterial infections, and maintain a moist environment for healing, but are surgically or mechanically debrided from the wound, causing additional trauma to the newly formed tissues. We have developed an on‐demand dissolvable dendritic thioester hydrogel burn dressing for second‐degree burn care. The hydrogel is composed of a lysine‐based dendron and a PEG‐based crosslinker, which are synthesized in high yields. The hydrogel burn dressing covers the wound and acts as a barrier to bacterial infection in an in vivo second‐degree burn wound model. A unique feature of the hydrogel is its capability to be dissolved on‐demand, via a thiol–thioester exchange reaction, allowing for a facile burn dressing removal. Abstract : An easily removable dressing : A hydrogel‐based dressing for second‐degree burn wounds has been synthesized and tested in vivo. It is composed of a dendritic macromonomer and a poly(ethylene glycol) crosslinker that form a hydrogel upon mixing. An on‐demand and atraumatic hydrogel dissolution proceeds through thiol–thioester exchange reaction in presence of a cysteine methyl ester solution.